(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
Samad Vurghun was actual for that period and poet gained great popularity. Samad Vurgun Poetry reflects human emotions which includes the a strong lyric with epic imagination poetry. Some of these works do not associate with modern period, however, it reflects the “view” of the Soviet period very well. In this point of view they are very important. Despite of any ideology Samad Vurgun had served, underlying nationalism, national identity, moral values stand in his works’ roots.